Evaluation of the physical, chemical and sensory properties - Guiné, Raquel (2015)
The main objective of the present work was to dry grapes of Crimson variety through different method- ologies in order to ﬁnd an alternative for the production of raisins. Different methodologies were used for drying: so- lar direct exposition in a greenhouse and in convective drying chambers with constant air ﬂow at two tem- peratures: 50 and 60 C. Some chemical analyses were made, namely for total sugars, acidity, total phenols, total anthocyanins and total tannins. Also some physical prop- erties were evaluated, speciﬁcally color and texture. A sensorial analysis of the dried products was undertaken to evaluate the acceptability by consumers. The raisins pro- duced by the different methodologies didn’t show sig- niﬁcant differences at the chemical and physical levels. However, it was observed that the dried samples contained higher amounts of total phenolic compounds, anthocyanins and tannins in comparison to the fresh grapes. Sensory evaluation result showed that dried grapes produced using different methodologies was similar to commercial raisins.